Understanding Learners' Satisfaction in Blended Learning among Undergraduate Students in Malaysia - Umi Kalsom, Masrom; Nik Aloesnita, Nik Mohd Alwi; Nor Hazlin, Nor Asshidin (Horizon Research Publishing, 2019)
Blended learning has extensively been used in many higher education institutions including Malaysia. Hence, instructors and institutions need to be well-equipped with adequate knowledge and skills, so that blended learning could be implemented successfully. This paper investigates the satisfaction among learners in blended learning environment at one of the universities in Malaysia through a survey study. The participants were 317 undergraduates enrolled in a blended learning course. The questionnaire was adapted from Zhai, Gu, Liu, Liang and Chin-Chung (2017) and Naaj, Nachouki and Ankit (2012). Descriptive statistics was employed to analyze the learners' demographic and their satisfaction towards blended learning. The results indicate that the learners' satisfaction towards blended learning employed at their institution was positive. This study also highlights several implications and recommendations that could anchor a greater understanding in the implementation of blended learning at higher institutions.